Evaluation of Drinking Water Quality Using Fuzzy Logic in Sulaimani City, Kurdistan, Iraq. - Ghafour, Zeren Jamal (Sulaimani Journal for Engineering Sciences, 2023)
Water quality assessment is crucial for maintaining the health and well-being of communities. In this study, Fuzzy Logic Water Quality Index (FWQI) utilized as a tool to assess the water quality in Sulaimani City, Kurdistan, Iraq. FWQI combines the flexibility and interpretability of fuzzy logic with the ability to handle imprecise and uncertain data, making it suitable for assessing complex systems such as water quality. Daily data of eleven water parameters from 14-water tanks location across Sulaimani city were evaluated for the duration of 2011 to 2021. The identified parameters includes pH, TDS, EC, TA, TH, Ca, Mg, Cl, Na, K, and SO4 . Fuzzy logic membership functions used to represent the linguistic variables associated with each parameter, allowing for the conversion of numerical data into fuzzy sets. A set of fuzzy rules established to map the fuzzy sets of the input parameters to an overall water quality index. The formulated rules were based on expert knowledge and existing water quality guidelines. The Fuzzy Logic Inference Index (FLII) outcomes were validated by comparing them with conventional water quality indices and expert judgments, demonstrating the effectiveness and accuracy of the proposed approach. The FWQI values of the study area showed that the drinking water quality of all selected tanks are suitable for drinking. The quality classes of water ranges between acceptable to desirable.
Keywords: Fuzzy Logic; Fuzzy Water Quality Index (FWQI); Water Quality; Sulaimani City